Toner

By optimizing the magnetic distribution in a specific area of ​​the cross-section of the toner particles, combined with the design of the response layer and the melting layer, the problems of toner quality stability and low-temperature fixing performance in the prior art are solved, and the problem of taking into account the stability of toner quality and low-temperature fixing performance is achieved under harsh environments efficient fixing and long-term stability.

CN111929999BActive Publication Date: 2024-12-13CANON KK
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202010401025.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-05-13
Filing Date
2020-05-13
Publication Date
2024-12-13
Estimated Expiration
2040-05-13

AI Technical Summary

Technical Problem

It is difficult to take into account the quality stability and low-temperature fixing performance of the existing toner during long-term durability. The distribution state of the magnetic body needs to be further improved to prevent the occurrence of image defects such as fog.

Method used

By densely distributing the magnets within a specific area of ​​the cross-section of the toner particles and sparsely distribute them on the more inner side, combined with the design of the response layer and the melt layer, the distribution of the magnets is optimized to prevent external additives from being embedded and improve melt spreading performance.

Benefits of technology

It effectively prevents the hindrance of low-temperature fixing performance and prevents image defects under harsh environments, improving the quality stability and fixing performance of toner in long-term use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111929999B_ABST
    Figure CN111929999B_ABST
Patent Text Reader

Abstract

The present invention relates to a toner. A toner includes toner particles containing a binder resin and a magnetic body, wherein in cross-sectional observation of the toner using a transmission electron microscope, when the area percentage occupied by the magnetic body in a region equal to or less than 200 nm from the outline of the cross section of the toner particle to the center of gravity of the cross section is taken as A1, and the area percentage occupied by the magnetic body in a region 200 nm to 400 nm from the outline of the cross section of the toner particle to the center of gravity of the cross section is taken as A2, the area percentage A1 is 38% to 85%, the area percentage A2 is 0% to 37%, and the ratio A2 / A1 of the area percentage A2 to the area percentage A1 is 0 to 0.75.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a toner suitable for use in an image forming method such as electrophotography. Background Art

[0002] In recent years, for electrophotographic image forming devices such as copiers and printers, high speed, long life, energy saving and miniaturization have been required, and in order to meet these requirements, various properties of toner need to be further improved. In particular, for toner, from the viewpoint of long life, quality stability needs to be further improved. In order to extend the life, it is important that the quality does not change significantly even during long-term durable use.

[0003] At the same time, further energy saving is required, and in particular, improvement in low-temperature fixing performance is urgently required for toner.

[0004] However, the improvement of quality stability performance and the improvement of low temperature fixing performance during long-term durable use tend to be in a compromise relationship. The method of adding silica fine particles with a large number average particle size or irregular silica fine particles, and the method of covering the surface of the toner particles with a hard surface layer are used to improve the quality stability performance during long-term durable use. However, these methods sometimes hinder the spreading of the toner on paper and reduce the low temperature fixing performance. In particular, since the low temperature fixing performance of a single color toner is greatly affected by the spreading of the toner on paper, it is a difficult task to improve the quality stability performance during long-term durable use without hindering the low temperature fixing performance of the toner.

[0005] To this end, Japanese Patent Application Publication Nos. 2008-15232 and 2017-102398 propose the following colorant, in which a material such as crystalline polyester is used inside the colorant to improve the low-temperature fixing performance, wherein a magnetic body is unevenly distributed near the surface of the colorant particles, thereby achieving both low-temperature fixing performance and quality stability during long-term durable use. Summary of the invention

[0006] However, even in the methods disclosed in the above patent documents, low temperature fixing performance and quality stability performance during long-term durable use are insufficient. In particular, it has been found that there is still room for research on the existence state of magnetic bodies, and further improvement is required.

[0007] An object of the present invention is to provide a toner that solves the above problems. Specifically, an object of the present invention is to prevent the low-temperature fixing performance of a toner using a magnetic body from being hindered and to prevent image defects such as fogging during long-term use under a severe environment.

[0008] A toner comprising toner particles containing a binder resin and a magnetic body, wherein

[0009] In cross-sectional observation of the toner using a transmission electron microscope,

[0010] wherein the area percentage occupied by the magnetic body in a region equal to or less than 200 nm from the outline of the cross section of the toner particle to the center of gravity of the cross section is taken as A1, and

[0011] The area percentage occupied by the magnetic body in the region from 200 nm to 400 nm from the outline of the cross section of the toner particle to the center of gravity of the cross section is taken as A2,

[0012] The area percentage A1 is 38% to 85%,

[0013] The area percentage A2 is 0% to 37%, and

[0014] The ratio A2 / A1 of the area percentage A2 to the area percentage A1 is 0 to 0.75.

[0015] According to the present invention, a toner using a magnetic body can be obtained in which the hindrance of low-temperature fixing performance can be prevented, and image defects such as fogging during long-term use under a severe environment can also be prevented.

[0016] Further features of the present invention will become apparent from the following description of exemplary embodiments with reference to the attached drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 is an example of a schematic diagram showing the existence state of a magnetic body inside a toner;

[0018] Figure 2 is a graphic representation of the propagation of stress caused by the magnetic body; and

[0019] Figure 3 is an image map of the mask used for image processing. DETAILED DESCRIPTION

[0020] Unless otherwise specified, the description of “above XX and below YY” or “from XX to YY” expressing a numerical range means that the numerical range includes the lower limit and the upper limit as endpoints.

[0021] As described above, for example, as a method of achieving both low-temperature fixing performance and quality stability performance during long-term durable use, a toner in which a magnetic body is unevenly distributed near the surface of a toner particle is proposed.

[0022] However, according to studies conducted by the present inventors, when paper having large irregularities such as rough paper is used in combination with high-speed and light-pressure fixing means, it is difficult to improve fixability only by using the above method.

[0023] It is revealed that this is because pressure and heat are not easily transferred to the toner in the concave portions of the paper in the fixing nip, and deformation and melt spreading of the toner in the concave portions of the paper in the fixing nip are prevented, thereby reducing the adhesion between the paper and the toner.

[0024] Therefore, in the case where the density of the magnetic body near the surface of the toner particles is increased in the above-described manner, in the concave portions of the paper, the melt spreading of the toner is hindered, and it is difficult to achieve both durability and low-temperature fixability.

[0025] Furthermore, according to studies conducted by the present inventors, it has been found that it is difficult to improve the quality stability performance during long-term durable use in a severe environment only by the above-mentioned method.

[0026] This is because, in the above method, the area where the magnetic body exists at a high density is widely distributed in the thickness direction of the toner, and in some parts, it is difficult to obtain the effect of improving the hardness by the magnetic body. As a result, when the particles of the toner having improved low-temperature fixing performance are repeatedly rubbed against each other or against the components in the developing unit in a harsh environment, that is, a high-temperature environment, the external additives existing on the surface of the toner particles are embedded in the toner particles.

[0027] Toner particles embedded with external additives come into contact with other toner particles or external additives more frequently, the fluidity of the toner decreases, and image quality is degraded due to insufficient charging, that is, image defects such as fogging occur.

[0028] As a result of intensive studies in consideration of these phenomena, the present inventors have proposed the following idea: in order to solve the above two problems simultaneously, it is necessary that the magnetic body exists densely within a certain distance range from the cross-sectional profile of the toner particle and exists sparsely further inside.

[0029] In addition, based on the results of in-depth research, the inventors have discovered that both low-temperature fixing ability and quality stability can be achieved by configuring a layer that is responsive to external force near the surface of the colorant particles (hereinafter referred to as the "responsive layer"), and configuring a layer that is easy to melt and spread in the layer below the responsive layer (hereinafter referred to as the "melting layer").

[0030] The present inventors consider this effect to be as follows.

[0031] First, the response layer will be described. As a result of friction between toner particles or between toner particles and a member in a developing unit, an external force is applied to an external additive fixed to the surface of the toner particle in a direction toward the inside of the toner particle, and an attempt is made to push the external additive inward. However, in the case where a magnetic body is arranged at a high density near the surface of the toner particle, the stress transmitted from the external additive to the toner particle is propagated and reflected by the magnetic body.

[0032] Therefore, the toner particles are quasi-hardened against the embedding of the external additive, and the embedding of the external additive is prevented. This effect is also shown when the magnetic body is not directly below the external additive. This is because the stress transmitted from the external additive to the toner particles spreads in the radial direction, and therefore, in the case where the density of the magnetic body is higher than a certain value, the surrounding magnetic bodies receive reflection of the stress, and the embedding prevention effect as described above can be obtained.

[0033] Next, the molten layer will be described. The fixability of the toner to paper depends on the degree of melt spreading on the paper. In particular, when the clamping time during fixing is short on paper with large irregularities such as rough paper, the melt spreading when no pressure is applied is a major factor. In addition, it is considered that this effect depends on the melt spreading performance of a portion present at a distance of about 400 nm from the surface of the toner particles.

[0034] Therefore, improving the melt spreading performance in such parts leads to improving the above-mentioned low-temperature fixing property. However, there is a concern that the above-mentioned response layer will hinder the melt spreading of the colorant when no pressure is applied. Therefore, it is necessary to improve the melt spreading in the area on the inside relative to the response layer and in the part corresponding to a distance of about 400nm from the surface of the colorant particle. A conceivable method for achieving this purpose involves making the magnetic body density equal to or lower than a specific value in the area on the inside relative to the response layer (magnetic body layer) and in the area (melting layer) up to 400nm from the surface of the colorant particle, which makes it possible to improve the melt spreading of the colorant when no pressure is applied.

[0035] As a result of intensive research conducted in consideration of these phenomena, the inventors have discovered that the above two problems can be solved simultaneously, and the present invention can be completed, by forming a magnetic layer in which the magnetic body is present at a high density within a specific distance range from the cross-sectional profile of the colorant particles, and by sparsely arranging the magnetic body on the inner side relative to the magnetic layer.

[0036] That is, the present invention relates to a toner comprising toner particles containing a binder resin and a magnetic body, wherein

[0037] In cross-sectional observation of the toner using a transmission electron microscope,

[0038] wherein the area percentage occupied by the magnetic body in a region equal to or less than 200 nm from the cross-sectional outline of the toner particle to the center of gravity of the cross section is taken as A1, and

[0039] The area percentage occupied by the magnetic body in the region from 200 nm to 400 nm from the cross-sectional profile of the toner particle to the center of gravity of the cross section is taken as A2,

[0040] The area percentage A1 is 38% to 85%,

[0041] The area percentage A2 is 0% to 37%, and

[0042] The ratio A2 / A1 of the area percentage A2 to the area percentage A1 is 0 to 0.75.

[0043] After the toner particles are processed into slices, the existence state of the magnetic body inside the toner particles is observed using TEM. In the cross-sectional image of the toner obtained by TEM observation, the region (response layer) equal to or less than 200 nm from the cross-sectional contour of the toner particle to the center of gravity of the cross section is the range obtained as follows.

[0044] That is, the length per unit pixel is calculated from the magnification and resolution of the TEM, and the number of pixels corresponding to 200 nm is calculated accordingly. Next, a boundary line is drawn from the outline of the cross section of the toner particle in a direction toward the center of gravity of the cross section at a distance of the number of pixels corresponding to 200 nm. The area from the boundary line to the surface of the toner particle is defined as an area equal to or less than 200 nm from the cross section outline of the toner particle to the center of gravity of the cross section (hereinafter referred to as area A).

[0045] Similarly, a region (molten layer, hereinafter referred to as region B) of 200 nm to 400 nm from the cross-sectional profile of the toner particle in the direction of the center of gravity of the cross section is determined (see Figure 1 ). The detailed process will be described later.

[0046] Figure 1 The symbols in are as follows.

[0047] 11: toner particle surface (contour line), 12: magnetic body, 13: (dashed line) boundary line from the contour to the position of 200 nm from the centre of gravity, 14: (dotted line) boundary line from the contour to the position of 400 nm from the centre of gravity, 15: inside of the toner particle.

[0048] When the area percentage of the magnetic body in the area of ​​the region A is taken as A1, the value of A1 needs to be 38% to 85%, and preferably 45% to 85%.

[0049] When the area percentage A1 is 38% or more, the magnetic body located near the surface of the toner particle is distributed within an appropriate distance and exists at a very short distance from the surface. Therefore, due to the effect of stress propagation of the force trying to embed the external additive, the vicinity of the surface of the toner particle is pseudo-hardened (see Figure 2 ).

[0050] As a result, the external additive present on the surface of the toner particles has a higher resistance to embedding due to friction between the toner particles and between the toner particles and the member during long-term durable use, and embedding of the external additive can be prevented. This effect is produced only when the external additive receives an external force. That is, this effect is produced only when friction occurs between the toner particles and between the toner particles and the member, so that a toner material that emphasizes fixability can be selected.

[0051] Meanwhile, in the case where the value of A1 is less than 38%, the distance between the magnetic bodies existing in the region A is large, and the proven effect of preventing embedding due to propagation of stress to the magnetic bodies cannot be obtained, and fogging may occur during long-term durable use under a harsh environment.

[0052] Furthermore, in the case where the value of A1 exceeds 85%, a resin component such as a binder resin hardly exists near the surface of the toner particle, so that the contact point between the paper and the toner becomes a magnetic body and melt spreading of the toner on the paper is hindered.

[0053] Figure 2 The symbols in are as follows.

[0054] 21: External additives, 22: Image of propagation stress range, 23: Magnetic body

[0055] When the area percentage of the magnetic body in the area of ​​the region B is defined as A2, the value of A2 needs to be 0% to 37%, and is preferably 0% to 29%.

[0056] When area percentage A2 is 37% or less, the amount of magnetic body present in region B is small and the viscosity of region B during fixing can be reduced. Therefore, the viscosity during fixing in the combined region of regions A and B is reduced and the melt spreading on paper can be improved.

[0057] Meanwhile, in the case where A2 exceeds 37%, the amount of magnetic body present in region B is large and the density is high, so that the viscosity during fixing increases in the combined region of regions A and B. Therefore, the toner is less likely to melt and spread on paper.

[0058] Furthermore, the value of the ratio of the area percentage A2 to the area percentage A1 (A2 / A1) needs to be 0 to 0.75, and is preferably 0 to 0.60.

[0059] In the case where A2 / A1 is 0.75 or less, both the effect of stress propagation in region A and the effect of improving melt spreading in region B can be achieved. Meanwhile, in the case where the value of A2 / A1 is greater than 0.75, the amount of magnetic body present in the region including region A and region B increases relative to the amount of magnetic body present in region A. As a result, the viscosity near the surface of the toner particles in the fixing nip increases, and melt spreading of the toner is hindered.

[0060] When the area percentage occupied by the magnetic body in the region (region inside region B) equal to or greater than 400 nm from the cross-sectional profile of the toner particle to the center of gravity of the cross section is taken as A3, the area percentage A3 is preferably 10% or less, and more preferably 5% or less. When the area percentage is 10% or less, when the toner is deformed in the fixing roller gap due to heat and pressure, the toner is easily deformed, and the fixing performance can be further improved. The lower limit is not particularly limited, but is preferably 0% or more.

[0061] The number average particle diameter D1 of the toner is preferably 4.0 μm to 10.0 μm, and more preferably 4.0 μm to 9.0 μm.

[0062] Within this range, viscous deformation due to interfacial tension of the toner present in the concave portions of the paper becomes a main phenomenon, and the above-mentioned effect of improving fixability by the value of A2 can be improved.

[0063] The binder resin is not particularly limited, and a known resin for toner can be used. Further, the binder resin preferably contains the resin B as a main component, and more preferably, the binder resin is the resin B. For example, the amount of the resin B in the binder resin is preferably 50% by mass to 100% by mass, more preferably 80% by mass to 100% by mass, and even more preferably 90% by mass to 100% by mass.

[0064] A specific example of the resin B is a vinyl resin.

[0065] The following monomers can be used in the production of the vinyl resin.

[0066] Aliphatic vinyl hydrocarbons: olefins such as ethylene, propylene, butene, isobutylene, pentene, heptene, diisobutylene, octene, dodecene, octadecene and other α-olefins; alkadienes such as butadiene, isoprene, 1,4-pentadiene, 1,6-hexadiene and 1,7-octadiene.

[0067] Alicyclic vinyl hydrocarbons: monocyclic or bicyclic olefins and alkadienes, such as cyclohexene, cyclopentadiene, vinylcyclohexene, ethylidene bicycloheptene; terpenes, such as pinene, limonene and indene.

[0068] Aromatic vinyl hydrocarbons: styrene and hydrocarbon (alkyl, cycloalkyl, aralkyl and / or alkenyl) substituents thereof, for example, α-methylstyrene, vinyltoluene, 2,4-dimethylstyrene, ethylstyrene, isopropylstyrene, butylstyrene, phenylstyrene, cyclohexylstyrene, benzylstyrene, crotylbenzene, divinylbenzene, divinyltoluene, divinylxylene and trivinylbenzene; and vinylnaphthalene.

[0069] Carboxyl-containing vinyl monomers and metal salts thereof: unsaturated monocarboxylic acids, unsaturated dicarboxylic acids, anhydrides and monoalkyl (1 to 27 carbon atoms) esters thereof having 3 to 30 carbon atoms. For example, carboxyl-containing vinyl monomers of acrylic acid, methacrylic acid, maleic acid, maleic anhydride, monoalkyl esters of maleic acid, fumaric acid, monoalkyl esters of fumaric acid, crotonic acid, itaconic acid, monoalkyl esters of itaconic acid, glycol monoethers of itaconic acid, citraconic acid, monoalkyl esters of citraconic acid, and cinnamic acid.

[0070] Vinyl esters such as vinyl acetate, vinyl butyrate, vinyl propionate, vinyl butyrate, diallyl phthalate, diallyl adipate, isopropenyl acetate, vinyl methacrylate, methyl 4-vinylbenzoate, cyclohexyl methacrylate, benzyl methacrylate, phenyl acrylate, phenyl methacrylate, methoxyvinyl acetate, vinyl benzoate, α-ethoxyethyl acrylate, alkyl acrylates and alkyl methacrylates having an alkyl group (linear or branched) having 1 to 22 carbon atoms (methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, butyl acrylate, butyl methacrylate, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, lauryl acrylate, lauryl methacrylate, myristyl acrylate, myristyl methacrylate, hexadecyl acrylate, hexadecyl methacrylate, stearyl acrylate, stearyl methacrylate, eicosyl acrylate, methacrylate acrylate, behenyl acrylate, and behenyl methacrylate, etc.), dialkyl fumarates (dialkyl esters of fumaric acid, the two alkyl groups are each independently a linear, branched or alicyclic group having 2 to 8 carbon atoms), dialkyl maleates (dialkyl esters of maleic acid, the two alkyl groups are each independently a linear, branched or alicyclic group having 2 to 8 carbon atoms), polyallyloxyalkanes (diallyloxyethane, triallyloxyethane, tetraallyloxyethane, tetraallyloxypropane, tetraallyloxypropane, tetraallyloxypropane, tetraallyloxypropane, tetraallyloxypropane, tetraallyloxypropane, tetraallyloxypropane, tetraallyloxypropane, tetraallyloxypropane, tetraallyloxypropane, tetraallyloxypropane, tetraallyloxypropane, tetraallyloxypropane, tetraallyloxypropane, diallyloxypropane, diallyloxypropane, propoxybutane and tetramethylallyloxyethane), vinyl monomers having a polyalkylene glycol chain (polyethylene glycol (molecular weight 300) monoacrylate, polyethylene glycol (molecular weight 300) monomethacrylate, polypropylene glycol (molecular weight 500) monoacrylate, polypropylene glycol (molecular weight 500) monomethacrylate, methanol ethylene oxide (hereinafter referred to as EO) 10 mol adduct acrylate, methanol ethylene oxide 10 mol adduct methacrylate, lauryl alcohol EO 30 mol adduct acrylate and lauryl EO 30 mol adduct methacrylate), polyacrylates and polymethacrylates (polyacrylates and polymethacrylates of polyols: ethylene glycol diacrylate, ethylene glycol dimethacrylate, propylene glycol diacrylate, propylene glycol dimethacrylate, neopentyl glycol diacrylate, neopentyl glycol dimethacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, polyethylene glycol diacrylate and polyethylene glycol dimethacrylate).

[0071] Carboxyl group-containing vinyl esters: for example, carboxyl alkyl acrylates having an alkyl chain having 3 to 20 carbon atoms, and carboxyl alkyl methacrylates having an alkyl chain having 3 to 20 carbon atoms.

[0072] Among them, copolymers of aromatic vinyl hydrocarbons and vinyl esters are preferred, and it is more preferred that the resin B contains a styrene acrylic resin. The styrene acrylic resin is preferably a copolymer of at least one selected from the group consisting of alkyl acrylates and alkyl methacrylates having an alkyl group (linear or branched) having 1 to 22 carbon atoms and styrene.

[0073] The toner particles contain a magnetic body.

[0074] Examples of magnetic bodies include magnetic iron oxides such as magnetite, hematite and ferrite, and magnetic iron oxides including other metal oxides; metals such as Fe, Co and Ni, or alloys of these metals with metals such as Al, Co, Cu, Pb, Mg, Ni, Sn, Zn, Sb, Be, Bi, Cd, Ca, Mn, Se, Ti, W, V, and mixtures thereof.

[0075] Among them, magnetite is preferred, and its shape may be polyhedron, octahedron, hexahedron, sphere, needle, and flake, etc. From the viewpoint of improving image density, shapes with small anisotropy such as polyhedron, octahedron, hexahedron, and sphere are preferred.

[0076] The number average particle diameter of the primary particles of the magnetic body is preferably from 100 nm to 300 nm, and more preferably from 150 nm to 250 nm.

[0077] The number average particle size of the primary particles of the magnetic substance present in the toner particles can be measured using a transmission electron microscope.

[0078] Specifically, after the toner to be observed is fully dispersed in the epoxy resin, the toner is cured for 2 days at a temperature of 40°C in the atmosphere to obtain a cured product. The cured product is used as a thin flaky sample obtained with a microtome, and an image with a magnification of 10,000 to 40,000 times is captured with a transmission electron microscope (hereinafter also referred to as TEM), and the projected area of ​​100 primary particles of the magnetic body in the image is measured. The equivalent diameter of a circle equal to the projected area is defined as the particle size of the primary particles of the magnetic body, and the average value of 100 particles is defined as the number average particle size of the primary particles of the magnetic body.

[0079] The amount of the magnetic body is preferably 40 parts by mass to 180 parts by mass based on 100 parts by mass of the binder resin. When the amount of the magnetic body is within the above range, the area percentages A1 and A2 can be easily controlled.

[0080] The amount of the magnetic body in the toner can be measured using a thermal analyzer TGAQ5000IR manufactured by Perkin Elmer Corp. In the measurement, the toner is heated from normal temperature to 900° C. at a temperature increase rate of 25° C. / min in a nitrogen atmosphere, the mass lost from 100° C. to 750° C. is taken as the mass of the component after the magnetic body is removed from the toner, and the remaining mass is taken as the mass of the magnetic body.

[0081] As a method for producing a magnetic body, the following can be exemplified.

[0082] An alkali such as sodium hydroxide is added to an aqueous ferrous salt solution in an amount equal to or greater than the iron component to prepare an aqueous solution containing ferrous hydroxide. Air is blown while the pH of the prepared aqueous solution is maintained at pH 7 or higher, and an oxidation reaction of the ferrous hydroxide is performed while the aqueous solution is heated to 70° C. or higher to produce seed crystals used as cores of a magnetic body.

[0083] Next, an aqueous solution containing an equivalent of ferrous sulfate based on the addition of the previous alkali is added to the slurry liquid containing the seed crystal. The reaction of ferrous hydroxide is carried out while the pH of the liquid is maintained at 5 to 10 while blowing air, and the magnetic iron oxide particles are grown with the seed crystal as the core. At this time, the shape and magnetic properties of the magnetic body can be controlled by selecting any pH, reaction temperature and stirring conditions. As the oxidation reaction proceeds, the pH of the liquid moves to the acidic side, but it is preferred that the pH of the liquid is more than 5. The magnetic body can be obtained by filtering the magnetic iron oxide particles obtained, washing and drying by conventional methods.

[0084] The magnetic body is preferably a hydrophobized magnetic body A hydrophobized using an alkyltrialkoxysilane coupling agent represented by the following formula (I) as a hydrophobizing agent. The hydrophobized magnetic body A has a magnetic body and a hydrophobizing agent on the surface of the magnetic body.

[0085] C p H 2p+1 -Si-(OC q H 2q+1 )3 (I)

[0086] In formula (I), p represents an integer of 4-16, and q represents an integer of 1-3.

[0087] It is preferred that p in the above formula is 4 or more because sufficient hydrophobicity can be imparted. Meanwhile, it is preferred that p is 16 or less because treatment can be uniformly performed on the surface of the magnetic body and aggregation of the magnetic body can be prevented.

[0088] The addition amount of the hydrophobizing treatment agent is preferably 0.3 parts by mass to 2.0 parts by mass, more preferably 1.5 parts by mass or less, and even more preferably 1.3 parts by mass or less, based on 100 parts by mass of the untreated magnetic body.

[0089] When using the above silane coupling agents, one silane coupling agent or a combination of multiple silane coupling agents can be used for treatment. When multiple silane coupling agents are used in combination, each coupling agent can be used individually or simultaneously for treatment. In addition, titanium coupling agents, etc. can be used in combination.

[0090] The method of the hydrophobic treatment is not particularly limited, but the following method is preferable.

[0091] In order to allow the hydrophobizing agent to react uniformly on the surface of the magnetic particles to exhibit high hydrophobicity, and at the same time, to allow hydroxyl groups to partially remain on the surface of the magnetic particles without complete hydrophobization, it is preferred to perform the surface treatment in a dry manner using a wheel mixer or a grinder.

[0092] Here, as the wheel kneader, Mix-Muller, Multi-Mul, Stotts mill, reflux kneader, Erich mill, etc. can be used, and Mix-Muller is preferably used.

[0093] When a wheel mixer or mill is used, three functions of compression, shearing and scraping can be exhibited.

[0094] By compression, the hydrophobic treatment agent between the particles of the magnetic body is pressed against the surface of the magnetic body, thereby improving the close adhesion and reactivity with the particle surface. By applying shear force to the hydrophobic treatment agent and the magnetic body respectively by shearing action, the hydrophobic treatment agent can be elongated, and the particles of the magnetic body can be broken to destroy aggregation. In addition, by scraping action, the hydrophobic treatment agent present on the surface of the magnetic body particles can be evenly spread as by a scraper.

[0095] As a result of demonstrating the above three effects continuously and repeatedly, the surface of each magnetic body particle can be uniformly treated while particle aggregates are broken up and separated into individual particles without reaggregation.

[0096] Generally, a hydrophobizing agent represented by formula (I) having a relatively large number of carbon atoms is unlikely to uniformly treat the particle surface of a magnetic body at a molecular level because the molecules of the agent are large and bulky, but treatment by the above method is preferred because the treatment can be performed stably.

[0097] When the surface treatment of the magnetic body is performed by using the hydrophobizing agent represented by formula (I) by a wheel mixer or a grinder, a particle surface of the magnetic body on which portions reacted with the hydrophobizing agent and residual unreacted hydroxyl groups alternately exist and coexist can be achieved.

[0098] By making the particle surface of the magnetic body in such a state, it is possible to improve the hydrophobicity and impart a certain water absorption property, and it is also possible to control the polarity of the magnetic body.

[0099] The toner particles preferably contain a resin C.

[0100] The resin C is preferably a non-crystalline polyester.

[0101] The amount of the resin C is preferably 1 part by mass to 50 parts by mass, more preferably 1 part by mass to 20 parts by mass, and even more preferably 2 parts by mass to 10 parts by mass relative to 100 parts by mass of the binder resin.

[0102] For the production of non-crystalline polyester resin, known monomers can be used. For example, divalent, trivalent or higher carboxylic acids and divalent, trivalent or higher alcohols can be used. Specific examples of these monomers are listed below.

[0103] Examples of the dicarboxylic acid include dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,11-undecanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,13-tridecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, 1,16-hexadecanedicarboxylic acid, 1,18-octadecanedicarboxylic acid, phthalic acid, isophthalic acid, terephthalic acid and dodecenylsuccinic acid, anhydrides thereof or lower alkyl esters thereof, and aliphatic unsaturated dicarboxylic acids such as maleic acid, fumaric acid, itaconic acid, and citraconic acid, etc. Lower alkyl esters and anhydrides of these dicarboxylic acids may also be used.

[0104] Examples of the trivalent or higher carboxylic acid include 1,2,4-benzenetricarboxylic acid, 1,2,5-benzenetricarboxylic acid, anhydrides thereof, lower alkyl esters thereof, and the like.

[0105] These may be used alone or in combination of two or more.

[0106] Examples of the diol include alkylene glycols (1,2-ethanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,20-eicosandiol); alkylene ether glycols (polyethylene glycol and polypropylene glycol); alicyclic diols (1,4-cyclohexanedimethanol); bisphenols (bisphenol A); alkylene oxide (ethylene oxide and propylene oxide) adducts of alicyclic diols, and alkylene oxide (ethylene oxide and propylene oxide) adducts of bisphenols (alkylene oxide adducts of bisphenol A).

[0107] The alkyl moiety of the alkylene glycol and the alkylene ether glycol may be linear or branched. Alkylene glycols having a branched structure can also be preferably used.

[0108] In addition, an aliphatic diol having a double bond may be used. Examples of the aliphatic diol having a double bond include the following compounds.

[0109] 2-Butene-1,4-diol, 3-hexene-1,6-diol and 4-octene-1,8-diol.

[0110] In addition, examples of the trivalent or higher alcohol include glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, and the like.

[0111] These may be used alone or in combination of two or more.

[0112] For the purpose of adjusting the acid value and the hydroxyl value, monobasic acids such as acetic acid and benzoic acid, and monohydric alcohols such as cyclohexanol and benzyl alcohol may be used as necessary.

[0113] Preferred are alcohol components such as bisphenols.

[0114] In addition, it is preferred that the non-crystalline polyester has a structure in which isosorbide is condensed. The structure in which isosorbide is condensed is represented by the following formula (A). In the case where the non-crystalline polyester includes such a structure, more magnetic bodies can be arranged uniformly in the region A. It is presumed that such an effect is produced because the relationship between the magnetic body, the binder resin, and the resin C is easily maintained appropriately by including the structure in which isosorbide is condensed.

[0115] For example, the non-crystalline polyester is prepared by condensing a dicarboxylic acid or its anhydride with isosorbide and a diol. Specifically, the non-crystalline polyester can be prepared by a dehydration condensation method at a reaction temperature of 180° C. to 260° C. in a nitrogen atmosphere at a composition ratio in which a carboxyl group remains. If necessary, a monovalent or divalent or higher alcohol other than isosorbide can be used in combination. In addition, a monovalent or trivalent or higher carboxylic acid component or its anhydride can be used.

[0116]

[0117] The toner preferably contains a crystalline material.

[0118] From the viewpoint of low temperature fixing property, the crystalline material preferably includes an ester-based crystalline material. The amount of the crystalline material is preferably 1.0 to 35.0 parts by mass, and more preferably 2.0 to 30.0 parts by mass relative to 100.0 parts by mass of the binder resin.

[0119] Having crystallinity means that a clear endothermic peak (melting point) is observed in differential scanning calorimetry DSC.

[0120] From the viewpoint of low temperature fixability, the crystalline material may include wax (releasing agent).

[0121] Known waxes can be used as the wax. Specific examples of the wax include the following.

[0122] Hydrocarbon waxes (for example, petroleum waxes such as paraffin, microcrystalline wax and petrolatum and their derivatives, montan wax and its derivatives, hydrocarbon waxes obtained by the Fischer-Tropsch process and their derivatives, polyolefin waxes represented by polyethylene and polypropylene and their derivatives), carnauba wax, candelilla wax and other natural waxes and their derivatives, and ester waxes, etc.

[0123] Here, the derivatives include oxides, block copolymers with vinyl monomers, and graft-modified products.

[0124] Examples of ester waxes include monoester compounds having one ester bond in one molecule, and polyfunctional ester compounds such as diester compounds having two ester bonds in one molecule, tetrafunctional ester compounds having four ester bonds in one molecule, and hexafunctional ester compounds having six ester bonds in one molecule.

[0125] The wax preferably includes at least one compound selected from the group consisting of monoester compounds and diester compounds.

[0126] Among them, since ester compounds tend to be linear and have high compatibility with styrene-based resins, monoester compounds are more excellent in low-temperature fixing ability.

[0127] Specific examples of the monoester compounds include waxes mainly containing fatty acid esters, such as carnauba wax and montanic acid ester wax; compounds obtained by partially or completely removing the acid component from such fatty esters, such as deacidified carnauba wax; compounds obtained by hydrogenating vegetable oils, etc.; methyl ester compounds having a hydroxyl group; and saturated fatty acid monoesters, such as stearyl stearate, behenyl behenate, etc.

[0128] Specific examples of the diester compound include dibehenyl sebacate, nonanediol dibehenate, behenyl terephthalate, stearyl terephthalate, and the like.

[0129] The wax may include other known waxes other than the above compounds. In addition, one wax may be used alone, or two or more waxes may be used in combination.

[0130] From the viewpoint of low temperature fixability, the crystalline material may include crystalline polyester.

[0131] The crystalline polyester is preferably obtained by reacting an aliphatic diol with an aliphatic dicarboxylic acid. Among them, a polycondensate of a monomer containing an aliphatic diol having 2 to 12 carbon atoms and / or an aliphatic dicarboxylic acid having 2 to 12 carbon atoms is preferred.

[0132] Examples of the aliphatic diol having 2 to 12 carbon atoms include the following compounds.

[0133] 1,2-ethanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, and 1,12-dodecanediol.

[0134] In addition, an aliphatic diol having a double bond may be used. Examples of the aliphatic diol having a double bond include the following compounds.

[0135] 2-Butene-1,4-diol, 3-hexene-1,6-diol and 4-octene-1,8-diol.

[0136] Examples of the aliphatic dicarboxylic acid having 2 to 12 carbon atoms include the following compounds.

[0137] Oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,11-undecanedicarboxylic acid, and 1,12-dodecanedicarboxylic acid. Lower alkyl esters and anhydrides of these aliphatic dicarboxylic acids may also be used.

[0138] Among them, sebacic acid, adipic acid and 1,10-decanedicarboxylic acid, and lower alkyl esters and anhydrides thereof are preferred. These may be used alone or as a mixture of two or more.

[0139] In addition, aromatic carboxylic acids may also be used. Examples of aromatic dicarboxylic acids include the following compounds. Terephthalic acid, isophthalic acid, 2,6-naphthalene dicarboxylic acid, and 4,4'-biphenyl dicarboxylic acid. Among them, terephthalic acid is preferred because it is easily available and easily forms a polymer with a low melting point.

[0140] A dicarboxylic acid having a double bond may also be used. A dicarboxylic acid having a double bond may be suitably used to prevent hot offset during fixing because the entire resin may be crosslinked using the double bond.

[0141] Examples of such dicarboxylic acids include fumaric acid, maleic acid, 3-hexenedioic acid and 3-octenedioic acid. Other examples include lower alkyl esters and anhydrides thereof. Among them, fumaric acid and maleic acid are more preferred.

[0142] The production method of the crystalline polyester is not particularly limited, and the crystalline polyester can be produced by a general polyester polymerization method in which a dicarboxylic acid component and a diol component are reacted. For example, the crystalline polyester can be produced by using a direct polycondensation method or an ester exchange method according to the kind of monomer.

[0143] The crystalline material preferably includes at least one selected from the group consisting of hydrocarbon wax, ester wax, and crystalline polyester, and more preferably includes hydrocarbon wax and at least one selected from the group consisting of ester wax and crystalline polyester.

[0144] In cross-sectional observation of the toner particles by a transmission electron microscope, domains of crystalline material are present in region B, and the number average diameter of the domains is preferably 20 nm to 300 nm, and more preferably 20 nm to 100 nm. The number of domains of crystalline material in region B is preferably 10 to 100, and more preferably 10 to 80.

[0145] When the number average diameter of the domains of the crystalline material is 20 nm or more, the crystalline state can be maintained and the fixing property can be effectively exerted. When the number average diameter is 300 nm or less, the number of interfaces between the crystalline material and the binder resin can be increased, and plasticization can be performed instantaneously during fixing, so that the low-temperature fixing property can be improved and the gloss unevenness can be prevented.

[0146] The average diameter of the crystalline material can be controlled by the kind of the crystalline material, and a production method in which the crystalline material is instantaneously cooled and crystallized from a state in which the crystalline material is compatible with a binder resin during toner production, and the like.

[0147] When the number of domains of the crystalline material is 10 or more, the interface between the crystalline material and the binder resin can be increased, and plasticization can be instantaneously performed during fixing, so that low-temperature fixability can be improved and gloss unevenness can be prevented. When the number of domains is 100 or less, the possibility of plasticization of the binder resin other than during fixing can be reduced, and storage properties can be improved.

[0148] The number of domains can be controlled by the kind and combination of the crystalline material, a production method in which the crystalline material is instantaneously cooled and crystallized from a state in which the crystalline material is compatible with a binder resin during toner production, and the like.

[0149] Next, the relationship between materials constituting the toner will be described.

[0150] It is preferred that the magnetic body includes the hydrophobized magnetic body A, the binder resin includes the resin B, and the toner particles include the resin C.

[0151] When the dipole interaction term of the Hansen solubility parameter of the hydrophobized magnetic body A is taken as a (MPa 1 / 2 ), the dipole interaction term of the Hansen solubility parameter of resin B is taken as b(MPa 1 / 2 ), and the dipole interaction term of the Hansen solubility parameter of resin C is taken as c(MPa 1 / 2 ), preferably the relationship represented by the following inequality (1) is satisfied:

[0152] b <a<c(1)。

[0153] Here, the "dipole interaction term of the Hansen solubility parameter" refers to a polarization term δp representing the energy generated due to the dipole interaction between the three parameters constituting the Hansen solubility parameter. The units of the dipole interaction terms a, b, and c of the Hansen solubility parameters described in this specification are MPa. 1 / 2 .

[0154] In the case where the dipole interaction term of the Hansen solubility parameter is controlled to satisfy the relationship of inequality (1), the binder resin including resin B, the hydrophobized magnetic body, and the resin C can be arranged at the optimal position in the toner particles. Since the magnitude of the dipole interaction term between the materials is in the order of inequality (1), polarization between the materials is caused and the materials are prevented from being arranged integrally, it is obvious that this effect is exerted. In addition, it is believed that even when the toner is used for a long time in a high temperature and high humidity environment (temperature: 32.5°C, humidity: 80%), the occurrence of fogging can be prevented while improving the rear end stain.

[0155] It is preferable that "a" is 1.0 to 3.0. It is preferable that "b" is 1.0 to 3.0, and more preferably 1.0 to 2.4. In addition, it is preferable that "c" is 4.0 to 8.0.

[0156] The value of "a" can be controlled by the surface treatment material and the treatment method of the magnetic body. In addition, "b" and "c" can be controlled by the molecular structure of the main component and side chain of the resin, etc.

[0157] In consideration of the relationship between the above three components, the case of producing toner particles by suspension polymerization will be described. Preferably, the toner particles are obtained by granulating a magnetic toner composition including a resin C, a hydrophobized magnetic body A, and a polymerizable monomer capable of forming a resin B in an aqueous medium, and polymerizing the polymerizable monomer. Therefore, there are steps of mixing, dissolving, and granulating these materials. However, due to the difference in hydrophobicity and specific gravity, the resin or polymerizable monomer and the magnetic body tend to be non-uniform, and it is difficult to control the toner structure even if the dissolving strength is increased.

[0158] Therefore, the present inventors believe that a good toner in which the vicinity of the surface of the toner particle is controlled to have a specific structure can be obtained by maintaining a balance of affinity between the resin B forming the structure of the toner particle, the hydrophobized magnetic body A, and the resin C. Specifically, the outermost surface of the toner particle is a layer of the resin C, and the second layer has a shell structure formed by a layer containing the hydrophobized magnetic body A.

[0159] When the above three components satisfy the relationship of inequality (1), a specific shell structure is easily formed, so that the hardness of the toner particle surface becomes sufficient, and when the toner is used for a long time under a high temperature and high humidity environment, the embedding of external additives can be prevented. Therefore, fogging during long-term use under a high temperature and high humidity environment can be prevented. As a result, even when the toner is used for a long time under a high temperature and high humidity environment, the reduction in developability can be further prevented.

[0160] The toner may include external additives.

[0161] Examples of external additives include metal oxide fine particles (inorganic fine particles) such as silica fine particles, alumina fine particles, titanium dioxide fine particles, zinc oxide fine particles, strontium titanate fine particles, cerium oxide fine particles, and calcium carbonate fine particles. In addition, composite oxide fine particles using two or more metals can be used, and two or more selected from these fine particle groups in any combination can also be used.

[0162] In addition, resin fine particles, or organic-inorganic composite fine particles of resin fine particles and inorganic fine particles may also be used.

[0163] The external additive more preferably has at least one particle selected from the group consisting of silica fine particles and organic-inorganic composite fine particles.

[0164] The silica fine particles can be exemplified by sol-gel silica fine particles prepared by a sol-gel method, aqueous colloidal silica fine particles, alcoholic silica fine particles, fumed silica fine particles obtained by a vapor phase method, and fused silica fine particles.

[0165] Examples of the resin fine particles include resin particles of vinyl resins, polyester resins, and silicone resins.

[0166] Examples of the organic-inorganic composite fine particles include organic-inorganic composite fine particles composed of resin fine particles and inorganic fine particles.

[0167] The amount of the external additive is preferably 0.1 parts by mass to 20.0 parts by mass relative to 100 parts by mass of the toner particles.

[0168] The external additive may be subjected to a hydrophobizing treatment with a hydrophobizing agent.

[0169] Examples of the hydrophobizing agent include chlorosilanes such as methyltrichlorosilane, dimethyldichlorosilane, trimethylchlorosilane, phenyltrichlorosilane, diphenyldichlorosilane, tert-butyldimethylchlorosilane, and vinyltrichlorosilane; alkoxysilanes such as tetramethoxysilane, methyltrimethoxysilane, dimethyldimethoxysilane, phenyltrimethoxysilane, diphenyldimethoxysilane, o-methylphenyltrimethoxysilane, p-methylphenyltrimethoxysilane, n-butyltrimethoxysilane, isobutyltrimethoxysilane, hexyltrimethoxysilane, octyltrimethoxysilane, decyltrimethoxysilane, decamethoxysilane, Dialkyltrimethoxysilane, tetraethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, phenyltriethoxysilane, diphenyldiethoxysilane, isobutyltriethoxysilane, decyltriethoxysilane, vinyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldimethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-chloropropyltrimethoxysilane, γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-(2-aminoethyl)aminopropyl trimethoxysilane, and γ-(2-aminoethyl)aminopropylmethyldimethoxysilane, etc.; silazanes, such as hexamethyldisilazane, hexaethyldisilazane, hexapropyldisilazane, hexabutyldisilazane, hexapentyldisilazane, hexahexyldisilazane, hexacyclohexyldisilazane, hexaphenyldisilazane, divinyltetramethyldisilazane, and dimethyltetravinyldisilazane, etc.; silicone oils, such as dimethyl silicone oil, methyl hydrogen silicone oil, methylphenyl silicone oil, alkyl-modified silicone oil, chloroalkyl-modified silicone oil, chlorophenyl-modified silicone oil, fatty acid-modified silicone oil, polyether-modified silicone oil, alkoxy Modified silicone oil, methanol-modified silicone oil, amino-modified silicone oil, fluorine-modified silicone oil, and terminal reactive silicone oil, etc.; siloxanes, such as hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, hexamethyldisiloxane, and octamethyltrisiloxane, etc.; fatty acids and their metal salts, such as undecanoic acid, lauric acid, tridecanoic acid, dodecanoic acid, myristic acid, palmitic acid, pentadecanoic acid, stearic acid, heptadecanoic acid, arachidic acid, montanic acid, oleic acid, linoleic acid, arachidonic acid and other long-chain fatty acids, as well as salts of the above fatty acids with metals such as zinc, iron, magnesium, aluminum, calcium, sodium, and lithium.

[0170] Among them, alkoxysilanes, silazanes, and silicone oils are preferably used because hydrophobization can be easily performed. One of these hydrophobizing treatment agents may be used alone, or two or more thereof may be used in combination.

[0171] The toner may contain various external additives in order to improve the fluidity and charging properties of the toner.

[0172] An example of a production method of the toner will be described below, but the example is not limitative.

[0173] In the present invention, the production method for maintaining the area percentages A1, A2 and A3 and A2 / A1 within the above ranges is not particularly limited, but it is preferred to produce the toner particles in an aqueous medium by dispersion polymerization, association aggregation, dissolution suspension, suspension polymerization, and emulsion polymerization. The suspension polymerization method is more preferred because the magnetic body can be easily configured to exist near the surface of the toner particles, so that a toner satisfying appropriate physical properties can be easily obtained. That is, the toner particles are preferably suspension polymerization toner particles.

[0174] In the suspension polymerization method, for example, a polymerizable monomer capable of forming a binder resin (resin B), a magnetic body, and, as required, a resin C, a crystalline material, a colorant, a polymerization initiator, a crosslinking agent, a charge control agent, and other additives are uniformly dispersed to obtain a polymerizable monomer composition. Then, by using an appropriate agitator, the obtained polymerizable monomer composition is dispersed and granulated in a continuous layer (e.g., an aqueous phase) containing a dispersion stabilizer, and then a polymerization reaction is performed using a polymerization initiator to obtain toner particles having a desired particle size.

[0175] As the polymerizable monomer, those described above as the monomer of the vinyl resin can be used. Preferred examples are listed below.

[0176] Styrene monomers, such as styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, p-methoxystyrene, and p-ethylstyrene.

[0177] Acrylates, such as alkyl acrylates (methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, n-propyl acrylate, n-octyl acrylate, dodecyl acrylate, 2-ethylhexyl acrylate, and stearyl acrylate, etc.), 2-chloroethyl acrylate, and phenyl acrylate, etc.

[0178] Methacrylates, such as alkyl methacrylates (methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, n-octyl methacrylate, dodecyl methacrylate, 2-ethylhexyl methacrylate, and stearyl methacrylate, etc.), phenyl methacrylate, dimethylaminoethyl methacrylate, and diethylaminoethyl methacrylate, etc.

[0179] Other monomers, such as acrylonitrile, methacrylonitrile and acrylamide. These monomers can be used alone or as a mixture.

[0180] Among the above monomers, styrene monomers are preferred to be used alone or in combination with other monomers such as acrylates and methacrylates, because the toner structure can be easily controlled and the development characteristics and durability of the toner can be easily improved. In particular, it is preferred that the binder resin contains 50% by mass or more of a styrene acrylic resin.

[0181] As the polymerization initiator used in the production of toner particles by the polymerization method, those having a half-life of 0.5h to 30h at the time of polymerization reaction are preferred. In addition, it is preferred to use the polymerization initiator in an amount of 0.5 to 20 parts by mass relative to 100 parts by mass of the polymerizable monomer. In such a case, a polymer having a maximum molecular weight of 5000 to 50000 can be obtained, and the toner can have preferred strength and appropriate melting characteristics.

[0182] Specific examples of polymerization initiators include azo or diazo polymerization initiators, such as 2,2'-azobis-(2,4-dimethylvaleronitrile), 2,2'-azobisisobutyronitrile, 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis-4-methoxy-2,4-dimethylvaleronitrile, and azobisisobutyronitrile, and peroxide polymerization initiators, such as benzoyl peroxide, methyl ethyl ketone peroxide, diisopropyl peroxycarbonate, cumene hydroperoxide, 2,4-dichlorobenzoyl peroxide, lauroyl peroxide, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxypivalate, di(2-ethylhexyl) peroxydicarbonate, and di(sec-butyl) peroxydicarbonate, and the like.

[0183] Among them, tert-butyl peroxypivalate is preferred.

[0184] When the toner is produced by a polymerization method, a cross-linking agent may be added.

[0185] From the viewpoint of easily obtaining the stress propagation effect, it is preferred that the crosslinking agent be a crosslinking agent that does not contain a highly rigid structure such as an aromatic hydrocarbon group such as a phenylene group.

[0186] The amount of the crosslinking agent added is preferably 0.05 to 15.00 parts by mass, and more preferably 0.10 to 3.00 parts by mass, relative to 100 parts by mass of the polymerizable monomer. More preferably, the amount is 0.20 to 2.50 parts by mass.

[0187] The aqueous medium in which the polymerizable monomer composition is to be dispersed may contain a dispersion stabilizer. As the dispersion stabilizer, known surfactants, organic dispersants, and inorganic dispersants can be used. Among them, inorganic dispersants are preferred because they have dispersion stability due to their steric hindrance, so that even if the reaction temperature is changed, the stability is hardly lost, washing is easy, and thus the toner is hardly adversely affected.

[0188] Examples of such inorganic dispersants include polyvalent metal phosphates, such as tricalcium phosphate, magnesium phosphate, aluminum phosphate, zinc phosphate, and hydroxyapatite; carbonates, such as calcium carbonate, and magnesium carbonate; inorganic salts, such as calcium metasilicate, calcium sulfate, and barium sulfate; and inorganic compounds, such as calcium hydroxide, magnesium hydroxide, and aluminum hydroxide.

[0189] The amount of the inorganic dispersant added is preferably 0.2 to 20 parts by mass relative to 100 parts by mass of the polymerizable monomer. The dispersion stabilizer may be used alone or in combination of two or more. In addition, 0.001 to 0.1 parts by mass of a surfactant may be used in combination.

[0190] When an inorganic dispersant is used, it may be used as it is, but in order to produce finer particles, fine particles of the inorganic dispersant may be produced and used in an aqueous medium.

[0191] For example, in the case of tricalcium phosphate, an aqueous solution of sodium phosphate and an aqueous solution of calcium chloride may be mixed under high-speed stirring to produce fine particles of water-insoluble calcium phosphate, which enables more uniform and finer dispersion.

[0192] Examples of the surfactant include sodium dodecylbenzene sulfate, sodium tetradecyl sulfate, sodium pentadecyl sulfate, sodium octyl sulfate, sodium oleate, sodium laurate, sodium stearate, potassium stearate and the like.

[0193] In the step of polymerizing the polymerizable monomer, the polymerization temperature is usually set to 40° C. or higher, preferably 50° C. to 90° C. When polymerization is performed within this temperature range, for example, a release agent or the like to be sealed inside is precipitated by phase separation, and encapsulation becomes more complete.

[0194] After polymerizing the polymerizable monomer, the following cooling step is preferably performed. The dispersion in which the toner particles are dispersed in the aqueous medium is heated to a temperature exceeding the melting point of the crystalline material. However, this operation is unnecessary if the polymerization temperature exceeds the melting point.

[0195] After the temperature is raised, the dispersion is cooled to around room temperature at a cooling rate of 3° C. / min to 200° C. / min (preferably 3° C. / min to 150° C. / min) to increase the crystallinity of the crystalline material.

[0196] After the cooling step, the dispersion may be heated to about 50° C. and subjected to heat treatment.

[0197] The heat treatment is preferably performed for about 1 hour to 24 hours, more preferably for about 2 hours to 10 hours.

[0198] The obtained polymer particles are filtered, washed and dried by a known method to obtain toner particles. The toner particles can be used as toner as they are. The toner can be obtained by mixing an external additive with the toner particles and attaching the external additive to the surface of the toner particles. A classification step can also be introduced into the production process to cut the coarse powder and fine powder contained in the toner particles.

[0199] Methods of measuring various physical properties of the toner of the present invention will be described below.

[0200] <Method for measuring number average particle diameter (D1) of toner>

[0201] The number average particle diameter (D1) of the toner is calculated as follows.

[0202] As a measuring device, a precision particle size distribution measuring device "Coulter Counter Multisizer" based on the pore resistance method and equipped with a 100 μm aperture tube was used. " (manufactured by Beckman Coulter, Inc.). Dedicated software "Beckman Coulter Multisizer 3 Version 3.51" (manufactured by Beckman Coulter, Inc.) was used to set measurement conditions and analyze measurement data. Measurement was performed with 25,000 effective measurement channels.

[0203] As the aqueous electrolyte solution used for measurement, a solution prepared by dissolving special grade sodium chloride in ion exchange water to a concentration of about 1% by mass, such as "ISOTON II" (manufactured by Beckman Coulter, Inc.) can be used.

[0204] Prior to measurement and analysis, the dedicated software was set as follows.

[0205] On the "Change Standard Operating Method (SOM)" screen of the dedicated software, set the total count in the control mode to 50,000 particles, the number of measurements to 1, and the value obtained using "Standard Particles 10.0 μm" (manufactured by Beckman Coulter, Inc.) as the Kd value. The threshold and noise level are automatically set by pressing "Threshold / Measurement Noise Level". In addition, set the current to 1600 μA, the gain to 2, the electrolyte solution to ISOTON II, and check "Rinse Orifice Tube After Each Run".

[0206] In the "Pulse to Particle Size Conversion Settings" screen of the dedicated software, the bin interval was set to the logarithmic particle size, the particle size bin was set to 256 particle size bins, and the particle size range was set to 2 μm to 60 μm.

[0207] The specific measurement method is described below.

[0208] (1) About 200 mL of electrolyte aqueous solution was placed in a 250 mL glass round bottom beaker dedicated to Multisizer 3, the beaker was placed in a sample holder, and stirred with a stirring rod at 24 rpm in a counterclockwise direction. Dirt and bubbles in the nozzle were removed by the "Rinse nozzle" function of the dedicated software.

[0209] (2) About 30 ml of an aqueous electrolyte solution was placed in a 100 mL glass flat-bottom beaker. Then, about 0.3 mL of a dilute solution obtained by diluting "CONTAMINON N" (a 10% by mass aqueous solution of a neutral detergent for washing precision measuring instruments composed of a nonionic surfactant, an anionic surfactant, and an organic detergent at pH 7, manufactured by Wako Pure Chemical Industries, Ltd.) with about 3 times the mass of ion exchange water was added thereto as a dispersant.

[0210] (3) An ultrasonic disperser "Ultrasonic Dispersion System Tetora 150" (manufactured by Nikkaki Bios Co., Ltd.) with a power output of 120 W was prepared, in which two oscillators with an oscillation frequency of 50 kHz were built in with a phase shift of 180 degrees. A total of about 3.3 L of ion-exchanged water was placed in the water tank of the ultrasonic disperser, and about 2 mL of CONTAMINON N was added to the water tank.

[0211] (4) The beaker of (2) above is placed in the beaker fixing hole of the ultrasonic disperser, and the ultrasonic disperser is started. Then, the height position of the beaker is adjusted so that the resonance state of the liquid surface of the aqueous electrolyte solution in the beaker is maximized.

[0212] (5) In a state where the electrolyte aqueous solution in the beaker of (4) above is irradiated with ultrasonic waves, about 10 mg of the toner is added little by little to the electrolyte aqueous solution and dispersed therein. Then, the ultrasonic dispersion treatment is further continued for 60 seconds. In the ultrasonic dispersion treatment, the water temperature in the water tank is appropriately adjusted to a temperature of 10° C. to 40° C.

[0213] (6) The electrolyte aqueous solution of (5) above in which the toner is dispersed is dropped into the round bottom beaker of (1) above which has been placed in the sample holder by using a pipette, and the measurement concentration is adjusted to about 5%. Then, measurement is performed until the number of particles to be measured reaches 50,000.

[0214] (7) The measurement data is analyzed with the dedicated software attached to the device, and the number average particle diameter (D1) is calculated. The "average diameter" on the "Analysis / Number Statistics (Arithmetic Mean)" screen obtained when setting the graph / (number %) in the dedicated software is taken as the number average particle diameter (D1).

[0215] <Number average diameter of primary particles of magnetic substance>

[0216] After the magnetic body to be observed is fully dispersed in the epoxy resin, curing is performed for 2 days in an atmosphere at a temperature of 40°C to obtain a cured product. The obtained cured product is sliced ​​with a microtome to obtain a thin sheet sample, and the particle size of 100 magnetic iron oxide particles in the field of view is measured with a transmission electron microscope (TEM) at a magnification of 40,000 times. Then, the number average diameter is calculated based on the equivalent diameter of a circle equal to the projected area of ​​the magnetic body. This method can be used not only to measure a magnetic body as a raw material, but also to measure a magnetic body present inside a toner by using the toner as a sample.

[0217] <Method for observing a cross section of a ruthenium-dyed toner by transmission electron microscopy (TEM)>

[0218] The cross-sectional observation of the toner using a transmission electron microscope (TEM) can be performed as follows. The cross-sectional observation of the toner is performed by staining with ruthenium. For example, the crystalline resin or the like contained in the toner is more stained with ruthenium than the non-crystalline resin such as the binder resin, so that the contrast becomes clear and easy to observe. Since the amount of ruthenium atoms varies depending on the strength of the staining, the strongly stained part includes many of these atoms, which cannot allow the electron beam to pass through, and becomes black on the observed image, and the weakly stained part easily allows the electron beam to pass through, and becomes white on the observed image.

[0219] First, the toner was sprinkled on a cover glass (Matsunami Glass Co., Ltd., corner cover glass, square No. 1) to form a single layer, and an Os film (5 nm) and a naphthalene film (20 nm) were coated as a protective film by using an osmium plasma coater (filgen, Inc., OPC80T).

[0220] Next, a PTFE tube (φ1.5 mm (inner diameter)×φ3 mm (outer diameter)×3 mm) was filled with a photocurable resin D800 (JEOL, Ltd.), and a cover glass was placed on the tube in such an orientation that the toner was in contact with the photocurable resin D800. After the resin was cured by irradiation with light in this state, the cover glass and the tube were removed to form a cylindrical resin in which the toner was embedded on the outermost surface.

[0221] The cylindrical resin was cut from the outermost surface at a distance equal to the radius of the toner (4.0 μm when the weight average particle diameter (D4) was 8.0 μm) using ULTRASONIC ULTRAMICROTOME (Leica Microsystems Inc., UC7) at a cutting speed of 0.6 mm / s, thereby cutting out a cross section of the toner. Next, cutting was performed to obtain a film thickness of 250 nm and a slice sample having a cross section of the toner was prepared. By cutting in this manner, a cross section of the center portion of the toner was obtained.

[0222] The obtained section sample was stained using a vacuum electron staining apparatus (filgen, Inc., VSC4R1H) in RuO 4 gas under an atmosphere of 500 Pa for 15 minutes, and TEM observation was performed using TEM (JEOL, Ltd., JEM2800).

[0223] Acquire an image with a TEM probe size of 1 nm and an image size of 1,024 pixels × 1,024 pixels. In addition, adjust the contrast of the detector control panel of the bright image field to 1425, the brightness to 3750, the contrast of the image control panel to 0.0, the brightness to 0.5, and the gamma to 1.00.

[0224] <Identification of Domains of Crystalline Materials>

[0225] Based on the TEM image of the cross section of the toner, the domain of the crystalline material is identified by the following process. In the case where the crystalline material (crystalline polyester and release agent) is available as a raw material, its crystal structure is observed in the same manner as the method of observing the cross section of the toner with a transmission electron microscope (TEM) in the case of ruthenium staining described above, and an image of the lamella structure of each crystal of the raw material is obtained. They are compared with the lamella structure of the domain in the cross section of the toner, and in the case where the layer spacing of the lamella is 10% or less, the raw material that forms the domain in the cross section of the toner can be determined.

[0226] <Separation of Crystalline Materials>

[0227] In the case where the raw materials of the crystalline material (crystalline polyester and release agent) are not available, the separation operation is performed as follows. First, the toner is dispersed in ethanol as a poor solvent for the toner, and the temperature is raised to a temperature exceeding the melting points of the crystalline polyester and the release agent. At this time, pressure may be applied as needed. At this time, the crystalline polyester and the release agent that have exceeded their melting points are melted. Thereafter, by performing solid-liquid separation, the mixture of the crystalline polyester and the release agent can be collected from the toner. By classifying the mixture according to each molecular weight, the crystalline material can be separated.

[0228] <Measurement of the Number Average Diameter of Domains of Crystalline Material>

[0229] Based on the TEM image, the number average diameter of the domains of the crystalline material is determined from the major axis of the domains of the crystalline material.

[0230] The major diameter of the domain of the crystalline material is measured based on a TEM image obtained by observing a cross section of the toner with a transmission electron microscope (TEM) under ruthenium staining. At this time, the cross section of 100 or more toner particles is observed. All domains are measured and the number average diameter is calculated.

[0231] <Measurement of the Number of Domains of Crystalline Material>

[0232] The number of domains of crystalline material contained in the toner section is measured in the same manner as the measurement of the number average diameter of the domains of crystalline material. This operation is performed on 100 or more toner sections, and the number of domains per toner section is taken as the number of domains of crystalline material.

[0233] <Measurement of Area Percentages A1, A2, and A3>

[0234] The method for measuring the surface distribution unevenness of the magnetic body in the cross section of the toner particle observed with a transmission electron microscope (TEM) is as follows.

[0235] Next, use the image processing software "ImageJ" (from https: / / imagej.Nih.gov / ij / The obtained TEM image is binarized. Thereafter, a circle equivalent diameter (projected area circle equivalent diameter) is obtained from the binarized image of the cross section, and a cross section in which the value of the circle equivalent diameter is included in the range of ±5% of the number average particle diameter (D1) (μm) of the toner is selected.

[0236] From the TEM image of the corresponding particle, the site other than the site required for measurement was masked using "ImageJ", and the area of ​​the unmasked region inside the toner outline and the total area of ​​the magnetic body present in the unmasked region were calculated. A method of obtaining the area percentage A1 using this method will be specifically described below.

[0237] First, binarization is performed in such a manner that the outline and the inside of an obtained TEM image of a toner particle cross-sectional profile (hereinafter, referred to as Image 1 ) are white, and other background portions are black (hereinafter, referred to as Image 2 ).

[0238] Next, in order to calculate the magnification of the mask, the length per unit pixel in the image 1 is calculated. Next, based on the calculated value, the number of pixels that fit the distance from the outline of the toner particle to the boundary line of the region A, that is, 200 nm (hereinafter, referred to as x1) is calculated. Similarly, the number of pixels that fit the toner particle diameter measured by using the above method (hereinafter, referred to as x2) is also calculated. Then, the magnification M of the mask is calculated by (x2-x1) / x2.

[0239] Next, Image 2 is reduced to the calculated magnification M (the reduced image is referred to as Image 3 ). At this time, unlike Image 2 , the toner particle outline and the inside are set to black, and the other background parts are set to white (become transparent).

[0240] Next, image 2 and image 3 are added. At this time, image 2 and image 3 are added using "ImageCalculator" which is a function of "ImageJ", and Figure 3 As shown, an image 4 is created in which a region from the outline of the toner particle to 200 nm toward the center of gravity of the toner particle is white, and the other portions are black. The area S1 of the white region in the image 4 is measured.

[0241] Next, the created image 4 and the above-described TEM image are added similarly using "Image Calculator" to create an image 5 in which the area other than the measurement site is masked. The image 5 is binarized, and the magnetic body area S2 in the mask is measured.

[0242] Finally, the area percentage A1 occupied by the magnetic body in region A is calculated by S2 / S1×100.

[0243] Regarding the area percentages A2 and A3, calculations were performed by the same procedure except that the range of the area was changed to 200 nm to 400 nm toward the center of gravity for A2 and from 400 nm to the center of gravity for A3. The cross sections of 100 toner particles were observed, and the arithmetic mean was adopted.

[0244] <Measurement Method of Dipole Interaction Term of Hansen Solubility Parameter>

[0245] The dipole interaction terms of the Hansen solubility parameters of the hydrophobized magnetic body A, resin B, and resin C were calculated as follows.

[0246] When the raw materials are available, first, the molecular structure of the raw material of the hydrophobizing agent and the molecular structure of each raw material of resin B and resin C are determined by SDS or the like. Based on the structural formula, the calculation software HSPiP (by http: / / pirika.com / JP / HSP / index.html Available) for calculation.

[0247] Furthermore, when raw materials cannot be directly obtained, or when measurement is performed on available toner, calculation can be performed by identifying constituent materials by using analytical instruments such as a nuclear magnetic resonance apparatus (NMR) and a gas chromatography / mass spectrometer (GC / MS).

[0248] Example

[0249] Hereinafter, the present invention will be described based on Examples, but the present invention is not limited thereto. In the following formulations, parts are by weight unless otherwise specified.

[0250] <Production Example of Resin C1>

[0251] A total of 100 parts of a mixture obtained by mixing raw material monomers other than trimellitic anhydride in the amounts shown in Table 1 below and 0.52 parts of tin di(2-ethylhexanoate) as a catalyst were placed in a polymerization tank equipped with a nitrogen introduction tube, a dehydration tube, and a stirrer. Next, after the interior of the polymerization tank was set to a nitrogen atmosphere, a polycondensation reaction was performed over 6 hours while heating at 200°C.

[0252] After the temperature was further increased to 210° C., trimellitic anhydride was added, the pressure in the polymerization tank was reduced to 40 kPa, and then the condensation reaction was further performed. Table 1 shows the dipole interaction term c of the Hansen solubility parameter of the obtained resin C1.

[0253] <Production Example of Resins C2 and C3>

[0254] Resins C2 and C3 were produced by carrying out the same operation as that of resin C1 by charging the raw material monomers in the amounts shown in the following Table 1. Table 1 shows the dipole interaction term c of the Hansen solubility parameters of the obtained resins.

[0255] [Table 1]

[0256]

[0257] The abbreviations in the table are as follows.

[0258] BPA (2 mol PO): Bisphenol A propylene oxide 2 mol adduct

[0259] EG: Ethylene glycol

[0260] TPA: Terephthalic acid

[0261] TMA: trimellitic anhydride

[0262] In addition, including the following table, the units of the Hansen dipole interaction term are (MPa 1 / 2 ).

[0263] <Production Example of Crystalline Material D1>

[0264] - 100.0 parts of sebacic acid

[0265] -1,9-nonanediol 100.0 parts

[0266] -Dibutyltin oxide 0.1 parts

[0267] The above materials were placed in a heated and dried two-necked flask, nitrogen was introduced into the container to maintain an inert atmosphere, and the temperature was raised while stirring. Thereafter, stirring was performed at 180° C. for 6 hours. Thereafter, while continuing to stir, the temperature was gradually raised to 230° C. under reduced pressure, and further maintained for 2 hours. When the mixture became viscous, the mixture was air-cooled to stop the reaction, thereby obtaining a crystalline material D1.

[0268] <Crystalline Materials D2 to D4>

[0269] Table 2 shows data related to crystalline materials D2 to D4.

[0270] [Table 2]

[0271] Crystalline material No. Material Name D1 Crystalline polyester D2 Dibehenyl Sebacate D3 Behenyl Behenate D4 Behenyl Stearate

[0272] <Crystalline Material E1>

[0273] As the crystalline material E1, hydrocarbon wax (HNP-51: manufactured by Nippon Seiro Co., Ltd.) was used.

[0274] <Production Example of Magnetic Iron Oxide 1>

[0275] A total of 55 liters of 4.0 mol / L sodium hydroxide aqueous solution and 50 liters of 2.0 mol / L Fe 2+ The aqueous solution of ferrous sulfate of 1.50 μm and 1.50 μm was mixed and stirred to obtain an aqueous solution of ferrous salt containing ferrous hydroxide colloid. The aqueous solution was maintained at 85° C. and an oxidation reaction was performed while blowing air at 20 L / min to obtain a slurry containing core particles.

[0276] After filtering and washing the obtained slurry with a filter press, the core particles are dispersed in water again and re-pulped. To the re-pulped liquid, sodium silicate is added in an amount of 0.20 mass % in terms of silicon relative to 100 parts of the core particles, the pH of the slurry is adjusted to 6.0, and stirred to obtain magnetic iron oxide particles having a silicon-rich surface. The resulting slurry is filtered and washed with a filter press, and further re-pulped with ion-exchanged water.

[0277] A total of 500 g (10% by mass relative to the magnetic iron oxide) of ion exchange resin SK110 (manufactured by Mitsubishi Chemical Corporation) was added to the reslurry liquid (solid content 50 g / L), and the mixture was stirred for 2 hours to perform ion exchange. Thereafter, the ion exchange resin was removed by filtering through a mesh, then filtered with a filter press, washed, dried and pulverized to obtain a magnetic iron oxide 1 having a number average diameter of 200 nm.

[0278] <Production Example of Magnetic Iron Oxide 2>

[0279] By changing the production conditions of the Magnetic Iron Oxide 1 in the Production Example of the Magnetic Iron Oxide 1, the Magnetic Iron Oxide 2 having a primary particle number average particle diameter of 160 nm as spherical magnetite particles was obtained.

[0280] <Production Example of Magnetic Iron Oxide 3>

[0281] By changing the production conditions of the Magnetic Iron Oxide 1 in the Production Example of the Magnetic Iron Oxide 1, the Magnetic Iron Oxide 3 having a primary particle number average particle size of 300 nm as spherical magnetite particles was obtained.

[0282] <Production Example of Magnetic Iron Oxide 4>

[0283] By changing the production conditions of the Magnetic Iron Oxide 1 in the Production Example of the Magnetic Iron Oxide 1, the Magnetic Iron Oxide 4 having a primary particle number average particle size of 350 nm as spherical magnetite particles was obtained.

[0284] <Production Example of Magnetic Iron Oxide 5>

[0285] By changing the production conditions of the Magnetic Iron Oxide 1 in the Production Example of the Magnetic Iron Oxide 1, the Magnetic Iron Oxide 5 having a primary particle number average particle diameter of 260 nm as spherical magnetite particles was obtained.

[0286] <Production of Silane Compound 1>

[0287] While stirring, a total of 30 parts of n-decyltrimethoxysilane was added dropwise to 70 parts of ion exchange water. Thereafter, the aqueous solution was maintained at a pH of 5.5 and a temperature of 55° C., and was dispersed for 120 minutes at a peripheral speed of 0.46 m / s using a dispersion blade to perform hydrolysis. Thereafter, the pH of the aqueous solution was adjusted to 7.0, and the solution was cooled to 10° C. to stop the hydrolysis reaction. Thus, an aqueous solution containing silane compound 1 was obtained.

[0288] <Production of Silane Compounds 2 to 5>

[0289] Using the alkoxysilanes shown in Table 3, aqueous solutions containing silane compounds 2 to 5 were obtained in the same manner as in the production method of the silane compound 1.

[0290] [Table 3]

[0291] Silane compound No. Raw materials for silane compounds 1 n-Butyltrimethoxysilane 2 n-Octyltrimethoxysilane 3 n-Decyltrimethoxysilane 4 Tetradecyltrimethoxysilane 5 Hexadecyltrimethoxysilane

[0292] <Production of Hydrophobized Magnetic Material A1>

[0293] A total of 10.0 kg of the Magnetic Iron Oxide 1 was charged into a Simpson Mix-Muller (MSG-0L model, manufactured by SINTOKOGIO, LTD.) and pulverized for 30 minutes.

[0294] Thereafter, 95 g of an aqueous solution containing silane compound 1 as a silane coupling agent was added to the apparatus, and the apparatus was operated for 1 hour to hydrophobize the particle surface of magnetic iron oxide 1 with the silane coupling agent, thereby obtaining hydrophobized magnetic body A1.

[0295] <Production of Hydrophobized Magnetic Substances A2 to A7>

[0296] In the production method of the hydrophobized magnetic body A1, the kind of the silane compound was appropriately changed, and the spraying amount of the silane compound was appropriately changed as shown in Table 4. As a result, the desired hydrophobized magnetic bodies A2 to A7 adjusted to the desired "amount of carbon derived from the silane compound" were obtained. The physical properties are shown in Table 4 below.

[0297] Regarding the treatment method, FM indicates a dry treatment method using a Mitsui Henschel Mixer (Mitsui Miike Kakoki Co., Ltd.), and wet treatment indicates treatment in a liquid.

[0298] [Table 4]

[0299]

[0300] The unit of the amount of carbon derived from the silane compound is "mass %".

[0301] <Production of Hydrophobized Magnetic Body A8>

[0302] After the magnetic iron oxide 1 was placed in a Henschel mixer (Mitsui Miike Kakoki Co., Ltd.), the silane compound 1 (in an amount of 1.12 mass % of the magnetic iron oxide 1) was added while being sprayed at a rotation speed of 34.5 m / s in a dispersed state.

[0303] Next, after being dispersed in the same state for 10 minutes, the magnetic body adsorbed with the silane compound 1 was taken out and dried while being allowed to stand at 160° C. for 2 hours, and a condensation reaction of the silane compound 1 was performed. Thereafter, a magnetic body passing through a sieve with an opening of 100 μm was obtained as a hydrophobized magnetic body A8. The physical properties are shown in Table 4.

[0304] <Production of Hydrophobized Magnetic Material A9>

[0305] A total of 1.50 parts of silane compound 1 was added as a silane coupling agent to magnetic iron oxide 5 (100 parts), and then stirred sufficiently. The produced magnetic iron oxide particles were washed, filtered and dried by a conventional method. Afterwards, a magnetic body passing through a sieve with an opening of 100 μm was obtained as a hydrophobized magnetic body A9. The physical properties are shown in Table 4.

[0306] <Production of Toner Particles 1>

[0307] A total of 450 parts of a 0.1 mol / L-Na3PO4 aqueous solution was added to 720 parts of ion exchange water, which was then heated to a temperature of 60°C, and then 67.7 parts of a 1.0 mol / L-CaCl2 aqueous solution was added to obtain an aqueous medium containing a dispersion stabilizer.

[0308]

[0309] The above materials were uniformly dispersed and mixed using an attritor (Nippon Coke Industry Co., Ltd.) The monomer composition was heated to a temperature of 60° C., and the following materials were mixed and dissolved therein to obtain a polymerizable monomer composition.

[0310] - Crystalline material D1 10.0 parts

[0311] - Crystalline material E1 5.0 parts

[0312] - 10.0 parts of polymerization initiator

[0313] (tert-Butyl peroxypivalate (25 mass % toluene solution))

[0314] The polymerizable monomer composition was put into an aqueous medium and granulated by stirring at 10000 rpm for 15 minutes in a N2 atmosphere at a temperature of 60° C. Then, the mixture was stirred with a paddle stirring blade, and a polymerization reaction was performed at a reaction temperature of 70° C. for 300 minutes.

[0315] After the reaction was completed, the temperature was raised to 98°C and distillation was performed for 3 hours to obtain a reaction slurry. Thereafter, as a cooling step, water at 0°C was poured into the suspension, and the suspension was cooled from 100°C to 30°C at a rate of 100°C / min, then heated to 50°C and allowed to stand for 6 hours.

[0316] The suspension was then naturally cooled to 25° C. at room temperature. The cooling rate at this time was 1° C. / min. Thereafter, hydrochloric acid was added to the suspension to perform sufficient washing to dissolve the dispersion stabilizer, followed by filtration and drying to obtain Toner Particles 1. The formulation is shown in Table 5.

[0317] [Table 5]

[0318]

[0319] <Production of Toner Particles 2 to 31>

[0320] Toner particles 2 to 31 were obtained by performing the same operation as that for producing toner particle 1, except that the types and amounts of magnetic body A, monomers constituting resin B, resin C, crystalline material D and crystalline material E, and the cooling rate in the cooling step were changed as shown in Table 5.

[0321] <Production Example of Toner 1>

[0322] A total of 0.3 parts of sol-gel silica fine particles having a primary particle number average particle diameter of 115 nm are added to 100 parts of Toner Particles 1, and mixed using an FM mixer (manufactured by Nippon Coke Industries, Ltd.).

[0323] Thereafter, 0.9 parts of fumed silica fine particles having a primary particle number average particle diameter of 12 nm obtained by treating hexamethyldisilazane and then treating with silicone oil and having a BET specific surface area value of 120 m 2 / g of hydrophobic silica fine particles, followed by mixing similarly using an FM mixer (manufactured by Nippon Coke Industries, Ltd.) to obtain Toner 1. The physical properties are shown in Table 6.

[0324] <Production Example of Toners 2 to 31>

[0325] Toners 2 to 31 were obtained in the same manner as in Production Example of Toner 1, except that the toner particles shown in Table 6 were used.

[0326] [Table 6]

[0327]

[0328] <Example 1>

[0329] The electrophotographic apparatus for evaluation was obtained by modifying an HP printer (HP LaserJet Pro M506dn) to increase the process speed by 1.3 times.

[0330] In addition, CF287X was used as a toner cartridge, 680 g of Toner 1 was filled, and the following evaluation was performed. The evaluation results are shown in Table 7.

[0331] <Evaluation 1: Evaluation of Friction Fixability>

[0332] Evaluation of friction fixability was performed in a low-temperature, low-humidity environment (temperature 15° C., relative humidity 10%), which is a severe environment for evaluating low-temperature fixability. This is because the temperature rise rate is low in the low-temperature, low-humidity environment of the fixing device.

[0333] By using rough paper COTTON BOND LIGHT COCKLE (basic weight 90g / m 2 ) was used as evaluation paper, and an image having a halftone portion was arranged at the rear end portion relative to the paper conveying direction for evaluation. The image density of the halftone portion was output in such a manner that it became 0.70. Next, the obtained image was rubbed back and forth 5 times with silbon paper under a load of 4.9 kPa, and the image density reduction rate before and after rubbing was measured. The lower the density reduction rate, the better the fixability. The criteria for judging the friction fixability are shown below. The evaluation results are shown in Table 7.

[0334] The image density was measured using a Macbeth reflection densitometer (manufactured by Macbeth Co.).

[0335] A: Concentration reduction rate is less than 5.0%

[0336] B: Concentration reduction rate is 5.0% or more and less than 10.0%

[0337] C: Concentration reduction rate is 10.0% or more and less than 15.0%

[0338] D: Concentration reduction rate is 15.0% or more

[0339] <Evaluation 2: Fogging Evaluation>

[0340] Assuming a long-term durability test, a horizontal line pattern with a printing rate of 1% was set to 2 sheets / job, and the next job was started after stopping the machine once between two jobs. In this mode, an image output test was performed on a total of 20,000 sheets, after which a white image was output and its reflectivity was measured using REFLECTMETER MODEL Tc-6DS manufactured by Tokyo Denshoku Co., Ltd. The durability was evaluated under a harsh high temperature and high humidity environment (40.0°C / 80%Rh) where external additives may be embedded.

[0341] At the same time, the reflectance of the transfer paper before forming the white image was measured in the same manner. The fogging was calculated from the reflectance before and after the white image was output using the following equation.

[0342] Fogging (reflectance) (%) = reflectance of transfer paper (%) - reflectance of white image (%).

[0343] The evaluation criteria for fogging are shown below. The evaluation results are shown in Table 7.

[0344] A: Less than 1.0%

[0345] B: 1.0% or more and less than 1.5%

[0346] C: 1.5% or more and less than 2.5%

[0347] D: 2.5% or more

[0348] <Examples 2 to 26 and Comparative Examples 1 to 5>

[0349] Table 7 shows the evaluation results of Toners 2 to 26 corresponding to Examples 2 to 26 and Toners 27 to 31 corresponding to Comparative Examples 1 to 5, which were performed in the same manner as in Example 1.

[0350] [Table 7]

[0351]

[0352] While the present invention has been described with reference to exemplary embodiments, it is to be understood that the invention is not limited to the disclosed exemplary embodiments.The scope of the following claims is to be accorded the broadest interpretation so as to encompass all such modifications and equivalent structures and functions.

Claims

1. A toner comprising toner particles containing a binder resin and a magnetic body, characterized in that In cross-sectional observation of the toner using a transmission electron microscope, The area percentage occupied by the magnetic body in the region from the outline of the cross section of the toner particle to the center of gravity of the cross section equal to or less than 200 nm is taken as A1, and When the area percentage occupied by the magnetic body in the region from 200 nm to 400 nm from the outline of the cross section of the toner particle to the center of gravity of the cross section is taken as A2, The area percentage A1 is 38% to 85%, The area percentage A2 is 0% to 37%, and A ratio A2 / A1 of the area percentage A2 to the area percentage A1 is 0 to 0.

75.

2. The toner according to claim 1, wherein When the area percentage occupied by the magnetic body in a region equal to or larger than 400 nm from the outline of the cross section of the toner particle to the center of gravity of the cross section is taken as A3, the area percentage A3 is 10% or less. 3 . The toner according to claim 1 , wherein a number average particle diameter D1 of the toner is from 4.0 μm to 10.0 μm. 4 . The toner according to claim 1 , wherein the primary particles of the magnetic body have a number average particle size of 100 nm to 300 nm.

5. The toner according to claim 1 or 2, wherein The magnetic body comprises a hydrophobized magnetic body A, The binder resin includes resin B, and The toner particles include a resin C, and The dipole interaction term of the Hansen solubility parameter of the hydrophobized magnetic body A is taken as a, and its unit is MPa. 1 / 2 , The dipole interaction term of the Hansen solubility parameter of the resin B is taken as b, and its unit is MPa 1 / 2 ,and The dipole interaction term of the Hansen solubility parameter of the resin C is taken as c, and its unit is MPa 1 / 2 In the case of The relationship expressed by the following inequality (1) is satisfied: b <a<c (1)。 6 . The toner according to claim 5 , wherein a dipole interaction term b of a Hansen solubility parameter of the resin B is from 1.0 to 3.

0. 7 . The toner according to claim 5 , wherein the resin B is a vinyl resin. 8 . The toner according to claim 5 , wherein a dipole interaction term c of a Hansen solubility parameter of the resin C is 4.0 to 8.

0.

9. The toner according to claim 5, wherein The resin C is a non-crystalline polyester, and The non-crystalline polyester includes a structure in which isosorbide is condensed.

10. The toner according to claim 1 or 2, wherein The toner particles include a crystalline material, and In cross-sectional observation of the toner using a transmission electron microscope, The number average diameter of the domains of the crystalline material present in the region of 200 nm to 400 nm from the outline of the cross section of the toner particle toward the center of gravity of the cross section is 20 nm to 300 nm, and The number of domains of the crystalline material present in the region is from 10 to 100. 11 . The toner according to claim 10 , wherein the crystalline material includes at least one selected from the group consisting of hydrocarbon wax, ester wax, and crystalline polyester. 12 . The toner according to claim 1 , wherein the toner comprises the toner particles and an external additive. 13 . The toner according to claim 1 , wherein the toner particles are suspension-polymerized toner particles.